Lights out - Patterson, James, 1947-; Grabenstein, Chris (Patterson, James, 1947- Daniel X novels, 2015)
"Daniel X is finally ready to take on the universe's most evil alien outlaw that killed his parents years ago, but he will need all his friends--and superpowers--to make it out alive"--